TRANSFORMASI MANUFAKTUR DI ERA INDUSTRI 4.0: PERAN TEKNOLOGI CERDAS, EKONOMI SIRKULAR, DAN PENGEMBANGAN SDM DALAM MENINGKATKAN KINERJA DAN KEBERLANJUTAN - Sumarsih, Rani Sri; Permatasari, Diah; Amyati, Amyati (Universitas Bina Bangsa, 2024)
This study presents a systematic literature review (SLR) to explore the role of Industry 4.0 technologies, circular economy practices, and human resource development (HRD) in enhancing performance and sustainability within the manufacturing sector. Using SLR methodology, 29 articles from accredited international journals published between 2018 and 2024 were curated and thematically analyzed based on stringent inclusion and exclusion criteria. The selected articles were organized into three main themes: Industry 4.0 Technologies, Circular Economy in Manufacturing, and HR Development and Employee Empowerment. Key findings indicate that the adoption of smart technologies, such as the Internet of Things (IoT) and artificial intelligence (AI), significantly enhances operational efficiency and competitiveness in manufacturing. Additionally, circular economy practices support sustainability through resource optimization and waste reduction. HR development plays a crucial role in facilitating technological adaptation, although challenges such as infrastructure limitations and technology-related anxiety remain significant barriers. This review concludes that collaboration among governments, companies, and educational institutions is essential to overcome these implementation challenges. Practical implications and recommendations for further research are provided to support more inclusive and sustainable adoption of Industry 4.0